Central Diabetes Insipidus in Refractory Antineutrophil Cytoplasmic Antibody-associated Vasculitis - Ohashi, Keiji (Intern Med, 2017)
We herein describe two cases of refractory antineutrophil cytoplasmic antibody-associated vasculitis (AAV) complicated with diabetes insipidus (DI) possibly related to hypertrophic pachymeningitis (HP). One patient had microscopic polyangiitis and HP, which were refractory to cyclophosphamide, azathioprine, rituximab, mycophenolate mofetil (MMF), and mizoribine. Remission was finally achieved with the use of etanercept, but DI occurred 5 years later. The other patient had granulomatosis with polyangiitis, which that was refractory to cyclophosphamide, methotrexate, MMF, and rituximab. DI subsequently developed, but was successfully treated with etanercept. Dura mater hypertrophy was macroscopically observed in the latter case.